Block copolymer compositions - NAKAMICHI YUKINORI; FUJIWARA MASAHIRO (2004)
本发明提供包括如下物质的组合物：(A)2-40重量份嵌段共聚物，该嵌段共聚物具有特定的结构；和(B)98-60重量份至少一种选自苯乙烯类树脂、聚烯烃类树脂和聚(亚苯基醚)类树脂的热塑性树脂，或沥青。这些组合物具有优异的高温贮存稳定性和低温特性以及在不同特性中的平衡。而且，它们具有带有很少凝胶的良好外观以及很好平衡的物理性能如耐冲击性。这些组合物适于用作薄膜如食品包装膜，用于层压的膜，和可热收缩膜，用于食品的托盘，光电设备部件等，以及模塑的透明片制品如起泡试验盒。 A subject for the invention is to provide an asphalt composition excellent in high-temperature storage stability and low-temperature characteristics and having an excellent balance among properties.Another subject is to provide a resin composition which has a reduced gel content, satisfactory appearance, and excellent balance among properties including impact resistance and is especially suitable for use as thin films such as food wrap films, films for laminating, and heat-shrinkable films or transparent sheet moldings such as trays for foods or for parts of light electrical appliances, etc., blister cases, or the like.